2011
DOI: 10.1002/app.36254
|View full text |Cite
|
Sign up to set email alerts
|

Fast photo‐switched wettability and color of surfaces coated with polymer brushes containing spiropyran

Abstract: An intelligent photo-responsive spiropyran (SP)-contained surface that combines reversible wettability conversion with photochromic behavior was prepared on etched silicon substrates by atom transfer radical polymerization. The heterocyclic ring cleavage of SP moieties under UV irradiation leads to the change of the surface wettability and color. Water contact angle (CA) of the prepared surfaces change from 138.8 6 1.3 to 42.7 6 1.7 after 5 min under 365 nm UV irradiation and recover to its original state afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…Similar to the previous studies, both in the solution as well as on the substrate surface, the transformation to the merocyanin isomer proceeded within 5 min under UV‐light irradiation. The reverse isomerization into the spiropyran isomer could be induced after 12 h in the dark resulting in a switching to the hydrophobic state . After UV‐light irradiation to yield the merocyanin isomer, the surface was allowed to reisomerize back into the spiro‐isomer overnight, resulting in Θ equi = 79° and Θ equi = 93°, respectively, which are in very good agreement with the CA values measured before irradiation.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Similar to the previous studies, both in the solution as well as on the substrate surface, the transformation to the merocyanin isomer proceeded within 5 min under UV‐light irradiation. The reverse isomerization into the spiropyran isomer could be induced after 12 h in the dark resulting in a switching to the hydrophobic state . After UV‐light irradiation to yield the merocyanin isomer, the surface was allowed to reisomerize back into the spiro‐isomer overnight, resulting in Θ equi = 79° and Θ equi = 93°, respectively, which are in very good agreement with the CA values measured before irradiation.…”
Section: Resultssupporting
confidence: 78%
“…Particularly interesting are polymers that are responsive to both light and temperature. In the past years, several reports were published on temperature‐responsive polymers, containing light‐responsive spiropyran moieties . Spiropyran derivatives are highly interesting candidates for the preparation of light‐sensitive polymers because they undergo a chemical photoisomerization induced by irradiation with UV light.…”
Section: Introductionmentioning
confidence: 99%
“…If the lateral polymer density is sufficiently high, surface brushes are formed, which provide unique molecular orientations and properties . With respect to photoresponsive polymer brushes, there are a number of examples for SI polymerizations of photochromic monomers such as spiropyrans and azobenzenes . They exhibit fascinating smart responsive functions; however, this review will not touch on them and focuses only to LC brush systems.…”
Section: Surface‐tethered Lc Brush Polymersmentioning
confidence: 99%
“…Consequently, higher permeation rates were estimated for samples having lower amount of protein adsorbed onto the surface (open form). Wang et al [29] demonstrated how the functionalization of surfaces with spiropyran molecules can be induced the fastest and highest change in wettability reducing the contact angle from 138.8±1.3° to 42.7±1.7° aft er 5 min under 365 nm UV irradiation and recovering to the original state aft er 20 min of visible light irradiation.…”
Section: Light-driven Switchingmentioning
confidence: 99%